Human rights conditions in Xinjiang, China 1978-2007 - Rogers, Roy Anthony (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This thesis analyses the human rights conditions in Xinjiang, China from 1978 till 2007. The thesis examines both the internal and external factors that have influenced China's policies on the human rights conditions in Xinjiang. The timeframe ranging between 1978 and 2007 highlights three different administrations. Therefore, the aim is to analyse the changes in the human rights condition in Xinjiang under three different administrations and the factors that have caused the changes. The human rights conditions in Xinjiang have never been consistent. The people in Xinjiang have experienced a rather 'turbulent' journey since the economic reforms began in China in 1978. The findings from this study suggest that the human rights conditions in Xinjiang have undergone several stages. First is the 'repressive' stage, which occurred during the Cultural Revolution prior to 1978. Second is the 'reform and liberalisation' stage that was initiated by Deng Xiaoping in the 1980s which improved the human rights conditions. However, this was followed by the 'decline' stage, where human rights and security conditions in Xinjiang started to deteriorate. In the mid-1990s, the Chinese government introduced the 'Strike Hard' policy and intensified its crackdowns in the province. The fourth and final stage is the 'regressive' stage. In the aftermath of the September 11th attacks in the United States, the Chinese government has made use of the incident to increase crackdowns in Xinjiang. During this stage, the Chinese government reverted to harsh policies. It should be pointed out that although these policies may not be as extreme as the policies adopted during the Cultural Revolution, they still impinged on the freedom and rights of the Uyghurs. This study therefore enhances the information on the 'ups and downs' regarding the human rights conditions in Xinjiang between 1978 and 2007. The findings also suggest that draconian policies such as the 'Strike Hard' are counterproductive because they worsen the human rights conditions and only further increase the hostility of the Uyghurs towards the Han Chinese. Unless the Chinese government genuinely adopts a fair and just policy towards its national minorities, peace will not be attained in Xinjiang. It also analyses the role of Uyghur diaspora to internationalise the human rights issues in Xinjiang and China's reaction towards the international pressures. Finally, it also provides recommendations to the Chinese government, the various Uyghur diaspora groups and the United States to improve the human rights conditions in Xinjiang.